Electronic Health Documentation using Integrated Nursing Education System: Nursing Students’ Experience, Perceptions, Attitudes and Intention to Use - Chan, K.G; Saloma, Pawi; Ong, M.F; Goh, S.C (Centre for Applied Learning and Multimedia UNIMAS, 2017)
Electronic health record (EHR) systems have been implemented in healthcare organizations in different countries including selected Malaysian hospitals in the last decade. Health professionals including nurses navigate EHR system in relation to patient history, nursing assessment and interventions, progress notes, vital signs, intakes-outputs, incident reports, physicians’ orders and so forth. Preparation of nursing students as the future professional nurses who would accept and utilize the EHR system proficiently for a safe delivery of healthcare practice is imperative. Through a cross-institutional memorandum of academic understanding in year 2015, the web application Integrated Nursing Education System (iNES), a simulated electronic health documentation, web-based application (at https://www.ines.sg) from the National University of Singapore (Kowitlawakul, 2014) has been made accessible to students in the Department of Nursing, Faculty of Medicine and Health Sciences (FMHS) of UNIMAS for teaching-learning purpose. This study aims to examine nursing students’ experience with the newly introduced technology and the extent of new learning that they may have gained. Students’ perceptions, attitudes, intention to use iNES and factors influencing their intention to use iNES for simulated EHR was also identified.